One-Year Weight Losses in the Look AHEAD Study: Factors Associated with Success - Wadden, Thomas A. (2009)
This report provides a further analysis of the first year weight losses in the Look AHEAD (Action for Health in Diabetes) study and identifies factors associated with success. Participants were a total of 5,145 men and women with type 2 diabetes who were recruited at 16 sites and randomly assigned to an intensive lifestyle intervention (ILI) or a control condition, Diabetes Support and Education (DSE). During year 1, participants in ILI received comprehensive diet and physical activity counseling in 42 group and individual sessions, compared with 3 educational sessions for DSE participants. As reported previously, at the end of the year, ILI participants lost 8.6% of initial weight, compared to 0.7% for DSE (p < 0.001). Within the ILI group, all racial/ethnic groups achieved clinically significant weight losses (≥ 5.5%), although there were significant differences among groups. For the year, ILI participants attended an average of 35.4 treatment sessions and reported exercising a mean of 136.6 min/week and consuming a total of 360.9 meal replacement products. Greater self-reported physical activity was the strongest correlate of weight loss, followed by treatment attendance and consumption of meal replacements. The use of orlistat, during the second half of the year, increased weight loss only marginally in those ILI participants who had lost < 5% of initial weight during the first 6 months and chose to take the medication thereafter as a toolbox option. The lifestyle intervention was clinically effective in all subsets of an ethnically and demographically diverse population.